Optoacoustic imaging—Applications and advancements of innovative imaging techniques Optoakustische Bildgebung – innovative Bildgebungsverfahren auf dem Vormarsch - Nau, T.; Schneider, S.; Aguirre, J.; Ntziachristos; Biedermann, T.; Darsow, U. (Hautarzt, 2021)
Optoacoustic imaging (OAB) has developed steadily in recent years. By means of partly pulsed light, in a wide variety of wavelengths, different colour carriers (chromophores) are excited to form sound waves. These in turn are detected by the newly developed systems and converted into three-dimensional images by means of various algorithms. The technique is characterised by a good ratio between contrast and penetration depth and can create macro-, meso- and microscopic images due to its scalability. Optoacoustic macroscopy broadly irradiates the area to be examined with laser light. This can produce images with a high penetration depth, but only with a moderate resolution. Clinically interesting fields of application are for example the results of sentinel lymph nodes (SLNs) examined ex vivo using macroscopic optoacoustics. Due to the ability of OAB to visualise melanin, the detection rate of metastases was superior to previous methods, but not to histology. The ability to visualise dermal and epidermal structures, especially vessels, with good resolution makes optoacoustic mesoscopy useful in the examination of inflammatory skin diseases and could contribute to the verification of the success of therapy, e.g., with biologics for psoriasis vulgaris or atopic eczema (AE), in the future. Optoacoustic microscopy, which has so far been limited mainly to preclinical in vivo research, could be used in the future to detect even finer vascular structures and their changes. The clinical possibilities of OAB seem to be of great benefit and continue to be the subject of intensive research.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Algorithms; Imaging; three-dimensional; Melanoma; Mesoscopy; Microscopy; Sentinel lymph node